Vulnerable Subjects : Ethics and Life Writing - Couser, G. Thomas (Book collections on Project MUSE., 2004)
In an exploration of a range of life-writing scenarios-from the celebrity to the ethnographicand a number of life-writing genres from parental memoir to literary case studies by Oliver Sacks, addresses complex contemporary issues, including investigation of the role of disability in narratives of euthanasia and exploration of the implications of the Human Genome Project for life-writing practices in any age when many regard DNA as a code that scripts lives and shapes identity. A concern throughout is the ethical implications of the political and economic, as well as the mimetic, aspects of life writing. [back cover].